2013
DOI: 10.1177/1071100713477607
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Technique Versus an Extensile Lateral Approach for Intra-Articular Calcaneal Fractures

Abstract: Level III, retrospective comparative case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
194
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(202 citation statements)
references
References 29 publications
3
194
2
3
Order By: Relevance
“…As we recently started performing calcaneal surgery more often by an even more extended lateral approach according to Freeman et al [28] and (in less complex fractures) via the sinus tarsi approach [29,30], the severe wound complication rates appear to have decreased. In the latter type of approach a wound complication rate of 29 % in the ELA versus 6 % in the less invasive sinus tarsi approach was described [31].…”
Section: Discussionmentioning
confidence: 99%
“…As we recently started performing calcaneal surgery more often by an even more extended lateral approach according to Freeman et al [28] and (in less complex fractures) via the sinus tarsi approach [29,30], the severe wound complication rates appear to have decreased. In the latter type of approach a wound complication rate of 29 % in the ELA versus 6 % in the less invasive sinus tarsi approach was described [31].…”
Section: Discussionmentioning
confidence: 99%
“…The extensile lateral approach, however, is often associated with soft tissue complications [4,5]. Minimally invasive treatment modalities have been established to avoid these complications, and, when performed by skilled surgeons, the clinical results are comparable and the risk of abnormal wound healing is lower [7,8,13,[22][23][24]. Furthermore, Chen et al concluded that minimally invasive screw osteosynthesis augmented with calcium sulphate cement results in a more rapid return to weight-bearing, diminished joint stiffness and increased patient satisfaction [13].…”
Section: Discussionmentioning
confidence: 99%
“…We believe intervention via locking plates and early weight-bearing does not lead to loss of correction and stabilization as others, even if minimal invasive techniques are performed. [4,18] Similarly, the amount of depression on posterior facet showed a slight loss from early postoperative X-ray to the last visit.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Closed reduction percutaneous fixation, open reduction via extensive or mini incision and internal fixation are the most common procedures. [3,4] The literature agrees that weight-bearing should be avoided roughly three months postoperatively due to the possible risk of collapsed talocalcaneal articular surface. [5,6] The introduction of locking plates in orthopedics has changed the biomechanical durability of bone and fracture.…”
mentioning
confidence: 99%